AFP-Inhibiting Fragments for Drug Delivery: The Promise and Challenges of Targeting Therapeutics to Cancers - Lin, Bo; Dong, Xu; Wang, Qiujiao; Li, Wei; Zhu, Mingyue; Li, Mengsen (Frontiers in Cell and Developmental Biology, 2021)
Alpha fetoprotein(AFP) plays a key role in stimulating the growth, metastasis and drug resistance of hepatocellular carcinoma(HCC). AFP is an important target molecule in the treatment of HCC. The application of AFP-derived peptides, AFP fragments and recombinant AFP(AFP-inhibiting fragments, AIFs) to inhibit the binding of AFP to intracellular proteins or its receptors is the basis of a new strategy for the treatment of HCC and other cancers. In addition, AIFs can be combined with drugs and delivery agents to target treatments to cancer. AIFs conjugated to anticancer drugs not only destroy cancer cells with these drugs but also activate immune cells to kill cancer cells. Furthermore, AIF delivery of drugs relieves immunosuppression and enhances chemotherapy effects. The synergism of immunotherapy and targeted chemotherapy is expected to play an important role in enhancing the treatment effect of patients with cancer. AIF delivery of drugs will be an available strategy for the targeted treatment of cancer in the future.